2019
DOI: 10.1016/j.janxdis.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration rates in Virtual Reality Therapy: An individual patient data level meta-analysis

Abstract: Ample evidence supports the use of Virtual Reality (VR) for anxiety disorders. Nonetheless, currently there is no evidence about moderators or potential negative effects of VR treatment strategies. An Individual Patient Data (IPD) approach was employed with 15 retrieved datasets. The current study sample was composed of 810 patients. Randomized control trials (RCTs) for each primary outcome measure were performed, in addition to moderator analyses of the socio-demographic variables. Deterioration rates were 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 114 publications
0
42
0
2
Order By: Relevance
“…Since the first clinical applications of VR technology in the early 2000's, meta-analyses have revealed that VRET is efficacious (3), and even on par with traditional exposure therapy (4). Importantly, results generalize to reduced fear of real-world stimuli (5), there are low rates of deterioration (6) and efficacy has been demonstrated also among adolescents (7). Clinicians appear to have a positive view of VR interventions (8)(9)(10), and some findings indicate that some patients may even prefer it to traditional exposure therapy when given a choice between the two, as well as lower rates of refusal (11).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first clinical applications of VR technology in the early 2000's, meta-analyses have revealed that VRET is efficacious (3), and even on par with traditional exposure therapy (4). Importantly, results generalize to reduced fear of real-world stimuli (5), there are low rates of deterioration (6) and efficacy has been demonstrated also among adolescents (7). Clinicians appear to have a positive view of VR interventions (8)(9)(10), and some findings indicate that some patients may even prefer it to traditional exposure therapy when given a choice between the two, as well as lower rates of refusal (11).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in practice, exposure to real phobic images produces higher activations and it also may require a greater effort to voluntarily inhibit emotional activation than exposure to virtual stimuli and consequently may lead to more escape behaviors. Although there are no conclusive data on this [39], given that VR phobic stimulus exposure activates fewer escape behaviors, lower attrition rates and more therapeutic adherence can be expected, as reported by other studies [7,9,39,40]. For this, according to our data, virtual phobic stimuli require two paradoxical properties: They must be as similar as possible to real stimuli to activate the mechanisms associated with fear responses, but at the same time, participants need to be able to identify them as virtual.…”
Section: Discussionmentioning
confidence: 67%
“…There are several reasons for this efficacy: VR is an intermediate step in graduated exposure, a safe condition in which to train patients to cope with real stimuli. VR also enhances exposure when VRET is combined with in vivo exposure [5][6][7][8][9][10]. Interestingly, two processes in the functioning of VR can be inferred from these explanations: VR accurately represents real stimuli (exposure process [8]), and VR is an opportunity to cope with a distressing stimulus (training process [11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this form of treatment exceeded those of the therapist-assisted interventions and were comparable to the effects of best psychological interventions reported in a meta-analysis of researches on phobia treatments. In a meta-analysis of studies on VR therapy of anxiety disorders prepared by Fernandez-Alvarez [11] were examined post-treatment deterioration rates. Findings show very low deterioration frequency, which leads to a conclusion that there are no harmful effects of using VR interventions in the treatment of anxiety disorder.…”
Section: Application Of Vr In the Treatment Of Anxiety Disordersmentioning
confidence: 99%